Calotropis procera induced ocular toxicity, manifestations and management – an observational study - Pandey, Nidhi; Sahu, Vijaya (International Journal of Medical Research and Review, 2015)
Introduction: Calotropis procera produces copious amounts of latex, which possesses several pharmacological properties. It produces severe inflammatory response on local application and its accidental instillation in the eye is associated with significant ocular morbidity. This is an observational study to assess the ocular toxicity of the latex of Calotropis procera and its management. Methods: 34 patients presenting to the ophthalmology department of a tertiary care centre of central India with exposure to the latex of Calotropis procera, were included in the study. Results: The main symptoms reported were burning, watering and discomfort. Corneal edema with striate keratopathy was found to be a universal manifestation with or without epithelial lesions and intraocular inflammation.The keratopathy showed good response to topical corticosteroids. Conclusion: Exposure to the latex of Calotropis procera is associated with significant ocular morbidity. The typical manifestation of striate keratopathy resolves with topical steroids. Simple health education in the form of hand washing, and avoiding eye contact and eye rubbing while plucking the flowers and leaves of Calotropis can prevent this injury.